Kandidasi Calon Anggota Legislatif Perempuan DPRD Kabupaten Tegal Pada Pemilu 2024 (Studi Kasus : DPC PDIP Kabupaten Tegal) - Destyanti, Riris Dwi; Rohman, Ahmad Zaki Fadlur (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The ratification of the Affirmative action policy and the Zipper system in the General Election in Indonesia has increased women's participation as legislative candidates. In the 2024 election in Tegal Regency, many women are running for office through the Indonesian Democratic Party of Struggle (PDIP). This research aims to identify and understand the candidacy process carried out by PDIP for female legislative candidates. This study uses a qualitative method with an explanatory case study approach. The analysis was carried out using the theory of Gideon Rahat and Reuven Y, "Candidate Selection Theory: Methods and Consequences" with four indicators used in the study. First, the selectorate indicator shows a tendency to an exclusive continuum. Second, the candidacy indicator also leads to the exclusive side. Third, decentralization shows that PDIP operates centrally at the national level with a focus on large sectors of social groups. Fourth, regarding voting versus appointment, PDIP uses an appointment system to choose candidates. The candidacy of female legislative candidates in PDIP prioritizes women who come from the party structure.